Capturing the Impact of Unobserved Sector‐Wide Shocks on Stock Returns with Panel Data Model1. Issue 295 (4th August 2015) - Hong, KiHoon Jimmy; Peng, Bin; Zhang, Xiaohui
Abstract : Unobserved sector‐wide common shocks cause the issue of cross‐sectional dependence (CSD) in panel data modelling of stock returns. In this study we apply two econometric techniques: the seemingly unrelated regression approach and a Bayesian estimator for panel data models with factor structural errors, to allow for CSD within a particular sector. By applying these models to monthly stock returns of S&P100 companies from six sectors over 10 years, we can capture and measure the heterogeneous impacts of not only observed individual company accounting fundamentals and market‐wide common shocks, but also unobservable sector‐wide common shocks. Results from the empirical study show that the impacts from both observed factors and unobserved sector‐wide common shocks vary markedly across companies. After controlling for observed accounting fundamentals and market‐wide common factors, a considerable proportion of the variation in stock returns can be attributed to unobservable sector‐wide common shocks.